2021
DOI: 10.3390/jof7060455
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Compounds from Mangrove Endophytic Fungus and Their Uses for Microorganism Control

Abstract: Mangroves are ecosystems with unique characteristics due to the high salinity and amount of organic matter that house a rich biodiversity. Fungi have aroused much interest as they are an important natural source for the discovery of new bioactive compounds, with potential biotechnological and pharmacological interest. This review aims to highlight endophytic fungi isolated from mangrove plant species and the isolated bioactive compounds and their bioactivity against protozoa, bacteria and pathogenic viruses. K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 147 publications
0
31
0
1
Order By: Relevance
“…Mangrove plants harbour diverse endophytic bacteria and fungi. Reviews on mangrove plant-associated microbial secondary metabolites revealed that the secondary metabolites possess promising pharmacological properties [ 8 , 9 , 10 , 11 ]. Unsurprisingly, mangrove endophytic microbes have been attracting the considerable attention of pharmacological investigators because of their bioactive secondary metabolites, especially when their host plants are also used as native traditional/folk medicines [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mangrove plants harbour diverse endophytic bacteria and fungi. Reviews on mangrove plant-associated microbial secondary metabolites revealed that the secondary metabolites possess promising pharmacological properties [ 8 , 9 , 10 , 11 ]. Unsurprisingly, mangrove endophytic microbes have been attracting the considerable attention of pharmacological investigators because of their bioactive secondary metabolites, especially when their host plants are also used as native traditional/folk medicines [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the variable environmental conditions in mangrove ecosystems may serve as excellent selectors for structurally distinct secondary metabolites with intriguing pharmacological effects. Along with their host plants, endophytic bacteria have also been reported to be a rich source of secondary metabolites with promising pharmacological properties [ 8 , 9 , 10 , 11 ]. Of these, many compounds exhibit potent biological activities and may be considered as lead compounds for further drug developments.…”
Section: Introductionmentioning
confidence: 99%
“…Two recent reviews on anti-infectives from mangrove endophytic fungi were published by Deshmukh et al in 2020 [33] and Cadamuro et al in 2021 [34]. Many of these fungi have been reported from China, primarily due to their research groups now studying mangrove endophytes instead of their medicinal plant hosts [35].…”
Section: Bioactive Compounds From Fungal Endophytes Of Mangrovesmentioning
confidence: 99%
“…Approximately 220 million people are infected by malaria, resulting in 435,000 deaths worldwide per annum. The emergence of drug-resistant malaria strains to classical synthetic drugs requires a continuous search for new compounds from alternative niches to introduce new and efficient therapies ( Cadamuro et al, 2021 ). Bacillisporin G ( 31 ) and macrosporusone B ( 33 ) produced by the fungus T. macrosporus displayed weak antimalarial activity against Plasmodium falciparum (IC 50 values were 8.07 and 10.28 μM, respectively) in comparison with positive control dihydroartemisinin (IC 50 value was 0.003 μM) ( Chaiyosang et al, 2019 ).…”
Section: Biological Activities Of Duclauxin Metabolitesmentioning
confidence: 99%